Dynamics of Inflation in Indonesia: The Role of CPI, E-Money, Money Supply (M1), and Exchange Rate - Puspitasari, Dewi; Yunian, AA; Raharti, Rini (Jurnal Ilmiah Akuntansi & Bisnis, 2024)
This research aims to compare the influence of the consumer price index (CPI), electronic money transactions (e-money), money supply (M1) and exchange rates on inflation in Indonesia between the periods before the pandemic and after the Covid-19 pandemic . This research is a quantitative research with 67 data samples obtained. The data used in this study is published on the official website of the Central Bureau of Statistics and Bank Indonesia. The analysis in this study uses the Chow Test and Error Correction Model with the Engle-Granger method and also multiple linear regression with the OLS method assisted by the Eviews 9 data processing software. The results of the Chow test show that the regression model is differentiated according to the period; before and after the pandemic. The results of the OLS test before the pandemic, the variable value of e-money transactions and the money supply affected the inflation rate, while the CPI, exchange rate, and BI rate were not affected. After Covid-19, the analysis results showed that the CPI, exchange rate, and BI Rate had a significant effect on the inflation rate. Meanwhile, the variable value of e-money transactions and the money supply has no effect on inflation rate in Indonesia.